Characteristics of knowledge translation theories, models and frameworks for health technology reassessment: expert perspectives through a qualitative exploration - Rosmin Esmail; Fiona M. Clement; Jayna Holroyd-Leduc; Daniel J. Niven; Heather M. Hanson (BMC, 2021)
Abstract Background Health Technology Reassessment (HTR) is a process that systematically assesses technologies that are currently used in the health care system. The process results in four outputs: increase use or decrease use, no change, or de-adoption of a technology. Implementation of these outputs remains a challenge. The Knowledge Translation (KT) field enables to transfer/translate knowledge into practice. KT could help with implementation of HTR outputs. This study sought to identify which characteristics of KT theories, models, and frameworks could be useful, specifically for decreased use or de-adoption of a technology. Methods A qualitative descriptive approach was used to ascertain the perspectives of international KT and HTR experts on the characteristics of KT theories, models, and frameworks for decreased use or de-adoption of a technology. One-to-one semi-structured interviews were conducted from September to December 2019. Interviews were audio recorded and transcribed verbatim. Themes and sub-themes were deduced from the data through framework analysis using five distinctive steps: familiarization, identifying an analytic framework, indexing, charting, mapping and interpretation. Themes and sub-themes were also mapped to existing KT theories, models, and frameworks. Results Thirteen experts from Canada, United States, United Kingdom, Australia, Germany, Spain, and Sweden participated in the study. Three themes emerged that illustrated the ideal traits: principles that were foundational for HTR, levers of change, and steps for knowledge to action. Principles included evidence-based, high usability, patient-centered, and ability to apply to the micro, meso, macro levels. Levers of change were characterized as positive, neutral, or negative influences for changing behaviour for HTR. Steps for knowledge to action included: build the case for HTR, adapt research knowledge, assess context, select interventions, and assess impact. Of the KT theories, models, and frameworks that were mapped, the Consolidated Framework for Implementation Research had most of the characteristics, except ability to apply to micro, meso, macro levels. Conclusions Characteristics that need to be considered within a KT theory, model, and framework for implementing HTR outputs have been identified. Consideration of these characteristics may guide users to select relevant KT theories, models, and frameworks to apply to HTR projects.